Silicon regulates the expression of vacuolar H+-pyrophosphatase 1 and decreases cadmium accumulation in rice (Oryza sativa L.). (February 2020) - Cao, Fangbin; Dai, Huaxin; Hao, Peng-Fei; Wu, Feibo
Abstract: Deciphering the mechanism of Cd accumulation in crops is imperative for minimizing soil-to-plant transfer of Cd to improve safe food production. Hydroponic experiments were performed examining Cd accumulation, growth performance and protein characteristics of two rice genotypes, Xiushui817 and Zheda821, with low and high grain Cd accumulation, respectively, under Cd stress and in the presence of Si. Xiushui817 had lower root-to-shoot Cd translocation and was more sensitive to Cd stress than Zheda821. Si reduced the shoot Cd content in both genotypes but more efficacy in Zheda821. Tandem mass tags (TMT)-based proteomic analysis identified 25 proteins associated with low grain Cd accumulation, including vacuolar H + -pyrophosphatase 1 (OVP1) that was up-regulated after Si addition in Zheda821. The sequence comparison of OVP1 showed one nucleotide difference in Xiushui817 relative to Zheda821 resulting in one amino acid. Overexpression of OVP1 reduced shoot Cd concentration and improved the growth of rice compared with WT under both control and Cd treatment. The results highlight the significant roles of OVP1 in both Cd accumulation and the Si-induced Cd reduction in rice. Our findings provide valuable insights into the molecular mechanism of low Cd accumulation and Si-induced decrease in Cd accumulation in rice. OVP1 could be used for transgenic overexpression in rice or other cereals for safe food production. Highlights: The first report proteomic study of grain low Cd accumulation in rice. Identified 25 proteins, including OVP associated with Si induced Cd decrease. Overexpression of OVP reduced shoot Cd level and improved rice growth. Novel genetic resource of grain low Cd accumulation in rice was verified.